Modulation of C5a-mediated effector functions of human polymorphonuclear leukocytes by tumor necrosis factor alpha and granulocyte macrophage colony-stimulating factor - Binder, Rolf; Kress, Alexander; Kirschfink, Michael (Experimental and clinical immunogenetics, 1999)
At the site of acute inflammation, leukocytes are confronted with multiple mediators which are expected to modulate each other with respect to cell responses to the individual ligand. In the present study, we compared the effects of the classical chemoattractants FMLP, PAF and LTB4, of the chemokine IL-8 and of TNFalpha, GM-CSF, IFN-gamma and IL-1beta on C5a-induced chemotaxis, degranulation, oxidative burst and expression of adhesion molecules of human neutrophils in vitro. Upon preincubation, TNFalpha as well as GM-CSF dose-dependently inhibited C5a-mediated chemotaxis, but augmented the release of elastase as well as respiratory burst activity. The effects of the two cytokines were accompanied by a downregulation of C5a receptors as determined by Scatchard analysis using (125)I-labeled C5a. Compared on a molar basis, TNFalpha was more effective than GM-CSF. C5a-induced expression of beta(2)-integrins was only moderately influenced by TNFalpha and GM-CSF. C5a itself diminished chemotaxis as well as degranulation and oxidative burst in response to a second dose of the same ligand (homologous desensitization), whereas heterologous desensitization by FMLP and IL-8 was restricted to C5a-induced degranulation or not observed (PAF, LTB4]. The cytokine effects are likely to be a consequence of altered C5a receptor expression as well as of postreceptor events. In concert with C5a, certain cytokines may shift neutrophil effector functions from migration to exocytosis, an essential step within the sequence of events in a coordinated inflammatory response.
Gesehen am 17.02.2021